Fatigue and durability of structural materials - Manson, S. S. (ASM International, 2006)
Fatigue and Durability of Structural Materials explains how mechanical material behavior relates to the design of structural machine components. The major emphasis is on fatigue and failure behavior using engineering models that have been developed to predict, in advance of service, acceptable fatigue and other durability-related lifetimes. The book covers broad classes of materials used for high-performance structural applications such as aerospace components, automobiles, and power generation systems. Coverage focuses on metallic materials but also addresses unique capabilities of important nonmetals. The concepts are applied to behavior at room or ambient temperatures; a planned second volume will address behavior at higher-temperatures. The volume is a repository of the most significant contributions by the authors to the art and science of material and structural durability over the past half century.-During their careers, including 40 years of direct collaboration, they have developed a host of durability models that are based on sound physical and engineering principles. Yet, the models and interpretation of behavior have a unique simplicity that is appreciated by the practicing engineer as well as the beginning student. In addition to their own pioneering work, the authors also present the work of numerous others who have provided useful results that have moved progress in these fields. This book will be of immense value to practicing mechanical and materials engineers and designers charged with producing structural components with adequate durability. The coverage is appropriate for a range of technical levels from undergraduate engineering students through material behavior researchers and model developers.-It will be of interest to personnel in the automotive and off-highway vehicle manufacturing industry, the aeronautical industry, space propulsion and the power generation/conversion industry, the electric power industry, the machine tool industry, and any industry associated with the design and manufacturing of mechanical equipment subject to cyclic loads.
Keywords: Building materials -- Fatigue.; Building materials -- Service life.; elektronické knihy; electronic books